EFL Learners from Hungary and EFL Pre-service Teachers from Colombia: A Narrative Research on Imagined Identities - Garzón Duarte, Eliana; Posada Ortiz, Julia Zoraida (Colombian Applied Linguistics Journal, 2020)
This article reports on a qualitative study that aims to explore on how the notion of imagined communities elucidates issues concerning identity and foreign language learning and teaching. The research questions that frame this study are the following: (1) What are the imagined identities (English as a Foreign Language (EFL)) students have constructed to learn English when enrolling in an English bachelor programme?, (2) How are these imagined identities connected to the imagined community they feel affiliated with? and (3) How are these imagined identities linked to the language practices of the EFL classroom? Narrative inquiry was used as the research method to answer these questions. Autobiographies were also written by the 26 participants enrolled in an English teacher education programme at a university in Colombia. Furthermore, written narratives and interviews were conducted with 15 students from an English bachelor programme at a university in Hungary. The study was conducted during one academic semester. The L2 motivational self-system theory, the theory of possible selves and the concepts of imagined communities and identities framed this research. Three salient categories emerged from the analysis of the narratives, namely, (1) bicultural identity: belonging to a worldwide community, (2) possible selves: broadening the scope of possibilities and (3) becoming an English teacher: an ongoing process.